Penyuluhan tentang Massase Uterus dan Pijat Oksitosin pada Ibu Nifas - Lina Contesa; Tri Restu Handayani (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The postpartum period is a phase from 2 hours after delivery to 6 weeks where the uterus shrinks (involutions) back to its pre-pregnancy size. The uterine involution process can be assisted with uterine massage. The results of Elisa's (2018) research on uterine fundus massage with health education using videos of uterine fundus massage on reducing uterine fundus height showed that there was an influence where the p value was 0.000 (<0.05). Massage the spine or what is known as oxytocin massage can stimulate the hormone oxytocin which functions for uterine contractions so that the uterus shrinks. Apart from stimulating contractions, the hormone oxytocin also plays a role in producing breast milk so that it can help the breastfeeding process. The aim of this activity is to provide information as well as teach postpartum mothers to perform uterine massage at home. This activity is carried out using demonstration methods via video and direct simulation by postpartum mothers. The results of the service were found from 15 counseling participants, 13 of whom could perform uterine massage well, 2 people did not understand. Community service activities that have educational value are very beneficial for postpartum mothers. For this reason, it needs to be improved and maximized by all parties involved.